Web-based carbon footprint calculator for bakery food waste / Nurul Fatihah Mohamed Yusof and Romiza Md Nor - Mohamed Yusof, Nurul Fatihah; Md Nor, Romiza (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Carbon footprint for food is greenhouse gas emissions produced by growing, farming, processing, transporting, storing, cooking, and disposing of food. Carbon emission is carbon gas that released every time food is produced. The term “food waste” is food that completes the food supply chain until the final product and suitable for human consumption but discarded regardless of whether it is rotten or expired. Wasting food means that greenhouse gas emissions that been released during food production are being wasted. Bakery is the biggest contributor in the food industry that contributes to food waste. Therefore, this project developed BakerCFC (Carbon Footprint Calculator) for bakery food waste. BakerCFC allows bakeries to effectively monitor carbon waste. User interface design for BakerCFC using persuasive technology which are reduction, suggestion, conditioning, self-monitoring, and surveillance. The methodology used in developing BakerCFC is Waterfall Model that consists of five phases which are analysis, design, development, testing, and documentation. Development of BakerCFC was using Bootstrap. The evaluation consists of functionality and usability testing of BakerCFC involving bakery owners and expert users. Usability evaluation was conducted to bakery owners for them to evaluate carbon footprint and motivate behavior change for three weeks. Two phases of usability testing were conducted that involved pre-evaluation and post-evaluation. Web-based carbon footprint calculators with persuasive technology aims to change behavior of bakery owners in reducing food waste. BakerCFC helped in changing behavior as well as motivating bakeries to reduce food waste.